Does Split-Body Resistance Training Routine Performed Two Versus Three Days Per Week Induce Distinct Strength and Morphological Adaptations in ResistanceTrained Men? A Randomized Longitudinal Study. (2022) - Brigatto, Felipe Alves; Camargo, Júlio Benvenutti Bueno De; Machado, Yuri Benhur; Germano, Moisés Diego; Aoki, Marcelo Saldanha
No abstract available